Transformed Lindley Distribution and Application for Acceptance Sampling Plan - Yimnak, Kanittha; Meechobtham, Panittha (Journal of Advanced Development in Engineering and Science, 2023)
A two-parameter Lindley distribution transformed using Log-expo transformation (LET-TLD) and involved one parameter for more flexible with lifetime distribution is proposed in term the probability density function, cumulative distribution function , survival function, hazard function, some moments and applying for real data, respectively. Then, the transformed distribution is applied for acceptance sampling plan (ASP) based on a truncated life test under LET-TLD. The developed ASP is presented along with the minimum sample sizes desired to testify that the specified mean life is attained, the values of operating characteristic function and the producer’s risk of ASP under LET-TLD. The results show that the developed ASP is gainful in producing lot.